Effects of intranasal infusion of glial derived neurotrophic factor (GDNF) nanoparticles on activation of dopamine neurons in opioid dependent rats - Lopes, Jenny-Lee (Tufts University. Tisch Library., 2023)
Opioid use disorder has no effective non-opioid-based drug treatments. These studies are ongoing and look at the effects of intranasal administration of glial derived neurotrophic factor plasmid DNA nanoparticles as a potential therapy for relapse prevention.; Cummings School of Veterinary Medicine Student Summer Research 2023.